Kajian Struktur Terowongan Proyek Bintaro Jaya Xchange Mall - Eko Walujodjati; Muhammad Zaki Fahmi; Mirza Fathir (Institut Teknologi Garut, 2025)
The construction of the tunnel structure of this mall project is intended for the construction of a tunnel under the Jakarta-Serpong toll road. This tunnel project has a length of 160 m and was built in 2022. The reason for taking this study was to determine how large the capacity is and prove that the tunnel structure is included in the safe and unsafe category of the structure. This research in this analysis was carried out using a manual calculation method and assisted by Microsoft Excel software to evaluate the structural strength, shear capacity, and moment capacity of the beam and column structures. As for the results of the study for the flexural reinforcement in the beam, the Mn value was obtained as 218370.52 KNm and Mu as 4572.55 kNm indicating that the structure or element has sufficient moment capacity to withstand the applied load. Furthermore, for the shear reinforcement, the Vs value is 1326.524 kN and the Vmax value is 1424.079 kN indicating that the shear force provided by the shear reinforcement (Vs) of 1326.524 kN is still below the maximum shear force that can be withstood by the element (Vsmax) of 1424.079 kN. While for the column structure section on the flexural reinforcement, the Pn value needs to be 481.23 kN and the Pnb value of 4,404.27 kN indicates that the structure has met the safety capacity and for the shear reinforcement, the Vu value is 156.40 kN and the value of 179.93 kN indicates that the structure has met the safety capacity. It can be concluded that the tunnel structure is safe and suitable for use by vehicles.